2019
DOI: 10.1111/jfbc.13068
|View full text |Cite
|
Sign up to set email alerts
|

Sumac ( Rhus coriaria ) for the prevention and treatment of necrotizing enterocolitis

Abstract: Leukotrienes, free oxygen radicals, tumor necrosis factor-alpha, and inflammatory mediators play major roles in the development of necrotizing enterocolitis (NEC). Rhus coriaria (RC: sumac) extracts may enhance cell viability by reinforcing defensesagainst free radical species in several progressive diseases as well as inflammatory diseases. The aim of the present study was to evaluate the effects of RC in a rat NEC model in terms of intestinal damage. Newborn pups were separated into three groups: control, NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In a recent investigation, Isik et al. (2019) investigated the effect of sumac water extract on the reduction of pathological mechanisms associated with the development of necrotizing enterocolitis (NEC) based on the bioactivity properties evidenced for R. coriaria extract including its anti‐inflammatory, anti‐apoptotic antibacterial and antioxidant properties . The results of this in vivo rat NEC model study showed that the levels of IL‐6 and TNF‐ α reduced significantly upon treatment with sumac revealing the anti‐inflammatory effect of suman in NEC …”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…In a recent investigation, Isik et al. (2019) investigated the effect of sumac water extract on the reduction of pathological mechanisms associated with the development of necrotizing enterocolitis (NEC) based on the bioactivity properties evidenced for R. coriaria extract including its anti‐inflammatory, anti‐apoptotic antibacterial and antioxidant properties . The results of this in vivo rat NEC model study showed that the levels of IL‐6 and TNF‐ α reduced significantly upon treatment with sumac revealing the anti‐inflammatory effect of suman in NEC …”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…In addition, sumac extract shows an anti-inflammatory effect against H. pylori bacterium, and could be used as an ingredient for food supplements to prevent inflammatory-based gastric diseases induced by H. pylori [33]. Moreover, a study suggests sumac as a new treatment option for preventing intestinal injury due to its anti-inflammatory activity in rat necrotizing enterocolitis model [34].…”
Section: Anti-bacterial and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…The red fruits of sumac are used as a very popular spice in Persian countries, either in their pure form or in combination with other spices, due to their sour lemon taste. According to the literature, sumac fruits possess a multitude of biological activities, including beneficial effects in vivo in streptozotocin-induced diabetes [23], lipid-lowering effects in hypercholesterolemic rats [24], cardioprotective effects in hyperlipidemic patients [25], and prevention of necrotizing enterocolitis [26]. Recently, our group demonstrated the beneficial effect of Rhus coriaria L. fruit extracts as preventive agents in the treatment of keratinocyte inflammation through their inhibition of skin pro-inflammatory mediators, including IL-8, MMP-9, ICAM-1, and VEGF [27].…”
Section: Recent Advances On the Role Of Polyphenols In Inflammatory Cmentioning
confidence: 99%